1995
DOI: 10.1152/jappl.1995.78.4.1425
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in intra-abdominal adipose tissue after strength training in older women

Abstract: The purpose of this study was to examine the effects of a total body strength-training program on changes in total and regional body composition, in particular intra-abdominal adipose tissue (IAAT), in older women. Fourteen healthy older women (mean age 67 +/- 1 yr) exercised 3 times/wk for 16 wk. Strength was assessed by one-repetition maximum tests, with training intensity gradually increased to approximately 67% of one repetition maximum. Body composition was measured by hydrodensitometry and regional body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
5
13

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 0 publications
8
93
5
13
Order By: Relevance
“…However, the visceral-to-subcutaneous ratio did not decrease within the diet and resistance trained groups. This ®nding is inconsistent with previous studies wherein for both men 5 and women, 6,35 resistance exercise is associated with a preferential reduction of visceral adiposity with 5,6 or without 35 weight loss. That the visceral-to-subcutaneous ratio did not decrease within the diet and resistance exercise groups is explained by the greater reduction in abdominal subcutaneous adipose tissue by comparison to the other treatments (Table 2).…”
Section: Discussioncontrasting
confidence: 97%
“…However, the visceral-to-subcutaneous ratio did not decrease within the diet and resistance trained groups. This ®nding is inconsistent with previous studies wherein for both men 5 and women, 6,35 resistance exercise is associated with a preferential reduction of visceral adiposity with 5,6 or without 35 weight loss. That the visceral-to-subcutaneous ratio did not decrease within the diet and resistance exercise groups is explained by the greater reduction in abdominal subcutaneous adipose tissue by comparison to the other treatments (Table 2).…”
Section: Discussioncontrasting
confidence: 97%
“…This latter observation is in agreement with another recent study that demonstrated that body weight change was the only significant correlate of changes in VAT in a small sample of morbid obese women after laparascopic surgery (Busetto et al, 2000). These results should however be interpreted with caution since some studies have also shown that significant changes in VAT can occur with very small changes in body weight when exercise is part of the intervention (Mourier et al, 1997;Schwartz et al, 1991;Thomas et al, 2000;Thong et al, 2000;Treuth et al, 1995). Since exercise has been shown to be related to an increase in sympathetic nervous system activity (Poehlman & Danforth, 1991;Tremblay et al, 1992), and that VAT has a greater lipolytic potential than SAT or TAT (Mauriège et al, 1987), it is possible that VAT may be reduced to a greater extent when exercise is part of the intervention.…”
Section: Dependent Variablesupporting
confidence: 89%
“…The fact that loss of weight was not different between the weight loss only group and the WL+RT was expected because loss of body weight is not typical with resistive training alone. 22 Yet, aerobic training can induce small amounts of fat mass loss, 23 so it is possible that a slightly greater loss of fat mass could have occurred in the WL+AEX group. As there were no differences in the amount of body weight or fat mass loss between the three groups, we were able to combine the women to assess changes in adiponectin with weight loss.…”
Section: Discussionmentioning
confidence: 99%